Sanguisorba officinalis L. suppresses non-small cell lung cancer via downregulating the PI3K/AKT/mTOR signaling pathway based on network pharmacology and experimental investigation - Hong Li; Hong Li; Jing Lin; Fei Yang; Junzhu Deng; Jia Lai; Jing Zeng; Wenjun Zou; Nan Jiang; Nan Jiang; Qianqian Huang; Qianqian Huang; et al. (Frontiers Media S.A., 2022)
Background: Non-small cell lung cancer (NSCLC) is the most common type of lung cancer. Sanguisorba officinalis L. (SOL), a traditional Chinese herbal medicine called Diyu, has been shown to have potent antitumor effects. However, the role of SOL in suppressing NSCLC remains unknown.Methods: Network pharmacology was employed for acquiring the potential targets and mechanisms of SOL in NSCLC. Based on the predictions of network pharmacology, we used CCK8 and EdU assays to investigate cell proliferation, flow cytometry to investigate apoptosis, wound healing assay to investigate cell migration, and transwell assay to investigate cell invasion in vitro. Western blot was employed for detecting the potential proteins, including signaling pathways and apoptosis. The A549-bearing athymic nude mice were employed to verify the effect on cell proliferation and apoptosis in vivo.Results: SOL significantly inhibited the proliferation, migration and invasion of NSCLC cells in a dose-dependent manner. Flow cytometry showed that the apoptotic ratio and ROS level of NSCLC cells increased significantly with increasing concentrations. AKT and the PI3K-AKT signaling pathway were analyzed as the most relevant target and pathway via network pharmacology predictions. Western blotting revealed that the expression levels of p-PI3K, p-AKT, and p-mTOR in NSCLC cells treated with SOL were significantly downregulated, while cleaved PARP-1 and caspase-3 were upregulated in a dose-dependent manner. The results in the mouse xenograft model were consistent with those in NSCLC cell lines.Conclusion: SOL downregulated the PI3K/AKT/mTOR signaling pathway to suppress NSCLC.